Optimization and characterization of quercetin-loaded solid lipid nanoparticles for biomedical application in colorectal cancer - Mohamed, Jamal Moideen Muthu; Ahmad, Fazil; El-Sherbiny, Mohamed; Al Mohaini, Mohammed Ahmad; Venkatesan, Krishnaraju; Alrashdi, Yahya Bin Abdullah; Eldesoqui, Mamdouh Basheir; Ibrahim, Adel Ehab; Dawood, Amal Fahmy; Ibrahim, Ateya Megahed; El Deeb, Sami (Cancer nanotechnology, 2024)
Background Colorectal cancer (CRC) is a type of cancer that affects the colon or rectum and occurs in individuals over the age of 50, although it can affect people of all ages. Quercetin is a flavonoid, which is a type of plant pigment with antioxidant and anti-inflammatory properties. Some studies have explored the potential of quercetin as an adjuvant therapy to enhance the effectiveness of chemotherapy or radiation therapy. Methodology In the proposed work, the nano-biomaterials of solid lipids such as stearic acid (SA) and tripalmitin (TpN) as well as the surfactants tween 80 and span 80 were used to prepare novel quercetin (QuR)-loaded-solid lipid nanoparticles (QuR-SLNs) for medical applications in colorectal cancer (CRC). The resulting bio-nano SLNs’ mean entrapment efficiency (EE) and particle size (PS) were optimized by Box–Behnken design (BBD) approach based on the response-like surface methodology (RSM). The variables include lipid ratio ( X 1 ), surfactant ratio ( X 2 ), QuR-to-lipid ratio ( X 3 ), the sonication time ( X 4 ), and the homogenization time ( X 5 ). Requirements on the maximum EE (%) and minimum PS (nm) were optimized for the preparation of QuR-SLN. Differential scanning calorimetry (DSC), X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM) were then used to analyze the optimized SLN and to find the crystalline state of QuR with lipid relationship. In addition, on the Caco-2 cells, at IC 50 (49 µM/mL), in vitro cytotoxicity was attained. Results The optimized QuR-SLN had practically spherical shapes, with % EE and a PS of 97.8 ± 1.16% and 132.16 ± 4.1 nm, respectively. In aqueous media, the degree of lipid crystallinity and the lipid modification was investigated, and the QuR incorporation and release patterns showed high correlations with both. The results showed that over 41.12 ± 1.6% of the bio-nano QuR-SLNs was released gradually over the course of 48 h, demonstrating effective QuR delayed release. Results on apoptotic observations indicate that apoptosis accounts for the majority of cell death, while necrosis, a type of cell death, constitutes a very minor portion. In conclusion, the prepared bio-nano QuR-SLNs might improve cytotoxicity and can act as an ideal carrier for the delivery of QuR and this preparation is used in the treatment of CRC.